2013
DOI: 10.1007/s12070-013-0670-6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Midline Cervical Cleft: A 7 Year Prospective Study

Abstract: Congenital cervical midline cleft (CCMC) is a rare disease of the head and neck region with only a few reported series. The patients attending the ENT or Plastic surgery OPD of a tertiary referral hospital of eastern India were screened for the presence of CCMC. All the patients found to have the developmental abnormality were included in the study and treated. Five patients were identified as having CCMC within the 7 year study duration. Of them three were female and two male. The youngest patient was a 2 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…Bergevin et al (1989) described the skin protuberance as a vertical outgrowth of the tongue muscle, since they found the fibrous cord was related to the fibrous median septum of the tongue base; salivary glands in the sinus tract and mucoid discharge contribute to this theory. Vascular anomalies causing ischemia, persistence of thyroglossal duct, and increased pericardial roof pressure are other embryological hypotheses (Genç et al, 2002;Saha et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bergevin et al (1989) described the skin protuberance as a vertical outgrowth of the tongue muscle, since they found the fibrous cord was related to the fibrous median septum of the tongue base; salivary glands in the sinus tract and mucoid discharge contribute to this theory. Vascular anomalies causing ischemia, persistence of thyroglossal duct, and increased pericardial roof pressure are other embryological hypotheses (Genç et al, 2002;Saha et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Midline cervical cleft has a prevalence of 2/1 in females. The most affected race is Caucasian (Saha et al, 2013). Etiology is thought to be related to a lack of fusion of the first and second branchial arches at an early stage of development (Saha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their retrospective case series of 8 patients, Achard et al [17] found only one patient with an atrophic kidney. Some authors found that CMCC can be associated with other anomalies like thyroglossal duct cyst [21], bronchogenic cyst [22], or a midline cleft from mandible to sternum [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although in the literature Z-plasty is the most commonly used way of incision closure in CMCC [17, 23, 24], we mostly used W-plasty (in 18 patients). In our experience, we found that it gave long-term satisfactory cosmetic and functional results.…”
Section: Discussionmentioning
confidence: 99%